Stressful Life Changes Affect Nutrition-Related Health Outcomes Among US Army Soldiers (P18-070-19). (13th June 2019) - Jayne, Julianna; Blake, Christine; Frongillo, Edward; Liese, Angela; Cai, Bo; Nelson, D Alan; Kurina, Lianne; Funderburk, LesLee
Abstract: Objectives: This prospective cohort study aimed to determine if experiencing stressful life changes were associated with an earlier onset of adverse nutrition-related health outcomes among US Army Soldiers. An additional aim was to determine which stressful life changes were most associated with these outcomes and if there were gender differences in the magnitude of the associations. Methods: Stressful life changes were changes in marital status, combat deployment or returning from deployment, relocation, adding a child, change in rank, change in occupation, or development of a physical limitation to duty. Nutrition-related health outcomes were hyperlipidemia diagnosis, substantial weight gain, or weight-related separation from the Army. Using longitudinal data from the Stanford Military Data Repository representing all active-duty Soldiers who were age 17–62 between 2011 and 2014 ( n = 827, 126), event history analysis was used to model the association of stressful life changes with nutrition-related outcomes. Results: Marriage was found to raise the odds of substantial weight gain three months later by 1.24 times (95% CI: 1.16, 1.32) for men and 1.68 times (95% CI: 1.51, 1.89) for women. Developing a physical duty limitation raised the odds of hyperlipidemia two months later by 1.42 times (95% CI: 1.15, 0.75) for men and 1.83 times (95% CI: 1.01, 3.32) for women and the odds of substantial weight gain two months later by 3.16 times (95% CI: 2.89, 3.44) in men and 1.69 times (95% CI: 1.36, 2.08) in women. Conclusions: Differences in the magnitude of associations show stressful life changes affect male and female Soldiers differently. Identifying times after stressful life changes when the risk of developing an undesirable health outcome is highest offers new possibilities for proactively addressing health. Findings could guide the timing of interventions to mitigate the effects of stress on health in military and civilian populations. Funding Sources: None. Disclaimer: Authors' views do not reflect official DoD or Army policy.